Theory and practice of International relations - McLellan, David S. (Englewood Cliffs, 1961)
This introduction to international relations provides a balance of academic views of leading scholars, as well as practical perspectives of world leaders. It considers both the traditional or classical balance-of-powers approach in addition to the newer global, human-problems approach - e.g., focusing on human rights, the environment, regimes and communication. This edition contains entirely new readings and introductions. It includes all the latest material on international relations theory and explores "the new world order" particularly the question of how the Clinton Administration will follow on from Bush's presidency.
Keywords: International Relations